Analisis Manajemen Risiko Operasional Pada Toko Baju - Amanda Nurussyifa,; Amirah, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The retail trade sector, particularly clothing stores, remains one of the main pillars supporting economic activity in urban and semi-urban areas. As conventional retail businesses, clothing stores face various operational risks that may affect business continuity, including inventory management, customer service, store security, and human resource management. If not properly managed, these risks can lead to financial losses and decreased customer satisfaction and loyalty. This study aims to describe the implementation of operational risk management in clothing stores based on questionnaire data collected from store owners and managers. A descriptive quantitative research method was employed, focusing on risk identification, evaluation, and control. The results indicate that clothing stores encounter diverse operational risks, particularly inventory mismanagement, product damage, theft, and suboptimal customer service. Although business owners are generally aware of these risks, risk management practices are still applied in a simple and unstructured manner. Therefore, a more systematic operational risk management approach is required to maintain business stability and ensure the sustainability of clothing store operations.